Polymeric PEI/PEG coated optical fiber fabry-perot interferometer for CO2 detection - Pawar, Dnyandeo; Lo Presti, Daniela; Lemma, Enrico D.; Rainer, Alberto; Kumar, Ajay; Kanawade, Rajesh; Silvestri, Sergio; Schena, Emiliano; Massaroni, Carlo (IEEE Sensors Journal, 2024)
Monitoring carbon dioxide (CO2) gas is essential for numerous applications, but the detection of CO2 in miniaturized devices presents significant challenges. In this study, a polyethyleneimine/poly(ethylene glycol) (PEI/PEG) coated optical fiber Fabry-Perot interferometer (FPI) and its charge transfer process toward CO2 are investigated. Scanning electron microscopy and Fourier transform infrared spectroscopy were used to analyze the surface morphology and vibration bands of the PEI/PEG composite. The PEI/PEG composite Fabry-Perot (FP) cavity of length similar to 13 mu m is coated at the distal end of the single-mode fiber using a dip coating technique. A highly sensitive optical and low-cost FPI probe fabrication has displayed a linear sensitivity of 17.10 nm/% in the range of 0.31%-1.25% CO2 gas. The response and recovery times of the sensor are in a few tens of seconds. The enhanced performance of the sensor is primarily due to the protonation and charge transfer between CO2 gas molecules and PEI/PEG composite. Due to low-cost fabrication and high sensitivity, this FPI sensor can be used in a range of potential applications in bioprocessing, healthcare, and environmental monitoring.
Keywords: dip coating; Fresnel's reflection; Interference; monitoring; Optical fiber sensors; Optical fibers; polymer composite; Polymers; refractive index; sensitivity; Sensor phenomena and characterization; sensors; swelling; Temperature sensors